2009
DOI: 10.2478/v10045-009-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Oyster Mushrooms for the Biocontrol of Sugar Beet Nematode (Heterodera Schachtii)

Abstract: Potential of Oyster Mushrooms for the Biocontrol of Sugar Beet Nematode (Heterodera Schachtii)The potential of oyster mushrooms to attack and kill sugar beet cyst nematode (Heterodera schachtii) was studied. The ability ofPleurotus ostreatus, P. sajor-caju, P. florida, P. flabellatus, P. ostreatus(sporeless),P. eryngiiandHypsizygus ulmariusto prey on the cyst nematode was confirmed. Nematodes were inoculated on water agar plates on which a single sparse fungal colony of one of the above mentioned fungi was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 11 publications
0
16
0
2
Order By: Relevance
“…Direct incorporation of MC into the soil could ensure direct contact of the mushroom mycelia with nematodes. Palizi, et al [57] reported that direct incorporation of oyster mushroom compost into the soil at 3% (w/w) suppressed more than 85% of sugar beet cyst nematode (Heterodera schachtii) cysts under ield conditions. On the other hand, Ching and Wang, et al [58] reported that direct MC amendment did not suppress M. incognita on basil roots in the sandy soil.…”
Section: Resultsmentioning
confidence: 99%
“…Direct incorporation of MC into the soil could ensure direct contact of the mushroom mycelia with nematodes. Palizi, et al [57] reported that direct incorporation of oyster mushroom compost into the soil at 3% (w/w) suppressed more than 85% of sugar beet cyst nematode (Heterodera schachtii) cysts under ield conditions. On the other hand, Ching and Wang, et al [58] reported that direct MC amendment did not suppress M. incognita on basil roots in the sandy soil.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that 11 species of fungi belonging to the order Agaricales, including Pleurotus ostreatus, have the ability to kill root-knot nematodes. Palizi et al [14] reported that this species reduced the formation of cysts from the nematode Heterodera schachtii and Marino and Silva [15], deduced that the use of Pleurotus ostreatus reduces the number of root-knot nematodes and egg mass of Meloidogyne incognita.…”
Section: Resultsmentioning
confidence: 99%
“…Limbah media jamur kancing (Agaricus bisporus) dilaporkan dapat menekan penyakit rebah semai pada seledri yang disebabkan oleh Phytophthora drechsleri (Goonani et al, 2011). Kompos bekas media jamur Tiram P. ostreatus dan P. sajor-caju dapat menekan jumlah sista Heterodera schachtii pada tanaman gula bit (Palizi et al, 2009). Limbah media jamur Hericium erinaceus dapat menekan penyakit layu bakteri yang disebabkan oleh Ralstonia solanacearum pada tanaman tomat (Kwak et al, 2015).…”
Section: Pendahuluanunclassified